Studying the effect of adding aqueous extracts of lemongrass and bay leaf on the chemical composition and microbial characteristics of frozen camel burger (Texas Journal of Agriculture and Biological Sciences, 2022)
The current study aimed to study the effect of adding aqueous extracts of lemongrass and bay leaves at concentrations (1-0.5%) on the chemical composition and microbial properties of camel burgers preserved in freezing at (-18°C) and for preservation periods (0-2-4-6) weeks. The results showed that there were no significant differences at the level (p